BRIDGING EDUCATIONAL GAPS: THE IMPACT OF THE BASS MODEL ON REFLEXIVITY AND CULTURAL HUMILITY IN MIDWIFERY STUDENTS - Lashea, Belinda Kay (East Carolina University, 2025)
ABSTRACT Midwifery education in the United States stands at a pivotal crossroads. While midwife-led care consistently demonstrates improved maternal and neonatal outcomes, particularly among racially and ethnically marginalized communities, the educational and clinical systems in which midwives are trained often emphasize efficiency, hierarchy, and compliance over reflection, presence, and relationship. This dissonance between midwifery philosophy and institutional reality fosters burnout, moral distress, and the erosion of reflective capacity, threatening the sustainability of the workforce and the ethical integrity of care. To meet these challenges, it is essential to implement pedagogical models within midwifery education and practice that emphasize reflection and humility as critical competencies for professional development. This dissertation examines whether structured reflection, guided by the Bass Model of Holistic Reflection, can foster reflexivity and cultural humility among graduate nurse-midwifery students. Reflexivity is defined as the sustained capacity to examine one’s values, biases, and positionality and to apply that awareness within dynamic care environments. Cultural humility is defined as a lifelong stance of openness, self-awareness, and relational accountability. Both are essential competencies for ethical, equitable, and culturally responsive midwifery practice. Despite their recognized importance, few empirical studies have investigated how these capacities evolve over time or how they can be intentionally cultivated through curriculum design. The Bass Model of Holistic Reflection builds on Schön’s reflection-in-action and reflection-on-action, Kolb’s Experiential Learning Cycle, and Mezirow’s Transformative Learning Theory to create a scaffolded process through which learners move from descriptive to critical and transformative levels of reflection. The model aligns with the Midwifery Model of Care, a humanistic paradigm that emphasizes relationship-based, person-centered care, cultural safety, and respect for physiologic processes, while offering a counterbalance to technocratic systems that privilege control and compliance. In this framework, reflection encompasses cognitive, emotional, and relational dimensions, fostering the development of reflexivity. Reflexivity (reflective capacity) subsequently contributes to the cultivation of cultural humility, the enhancement of professional resilience, and the maintenance of ethically sound practice. This research represents the first pilot of the Bass Model within a U.S. graduate midwifery program. Employing a longitudinal, quasi-experimental design, the study tracked sixteen students over two semesters in an ACME-accredited graduate nurse-midwifery program in the southeastern United States. Structured reflection was incorporated into both academic and clinical work through scaffolded journals, peer circles, and faculty debriefs, all carefully aligned with the Bass Model's six phases. To triangulate data and ensure a robust evaluation of reflexivity and humility among graduate nurse-midwifery students, three validated instruments were employed: the Cultural Humility Scale–Adapted (CHS-A), which captured students’ self-perceived humility and relational stance; the Holistic Reflection Self-Assessment (HRSA), measuring self-reported reflective capacity and depth; and the Modified Holistic Reflection Assessment Tool (MHRAT), a faculty rubric designed to assess observable reflective growth and developmental stage. Utilizing these measures in concert provided a multidimensional perspective, integrating both student self-perception and faculty observation to comprehensively track the development of reflexivity and humility over time. Quantitative analyses included descriptive statistics, paired-samples t tests, nonparametric Friedman tests, and Pearson correlations. Results demonstrated a statistically significant increase in faculty-rated reflective depth across five structured activities, χ² (4) = 16.81, p = .002, validating the Bass Model’s effectiveness in fostering reflexivity. HRSA scores remained high throughout the study, with a modest yet significant increase in the first semester, t (14) = 2.25, p = .041, d = 0.58, followed by a moderate, non-significant rise in the second. CHS-A scores increased slightly from pretest (M = 4.73, SD = 0.35) to posttest (M = 4.89, SD = 0.20), though ceiling effects limited measurable change. Correlational analyses revealed modest alignment between self- and faculty assessments, emphasizing the value of mixed-method evaluation. A moderate negative correlation between HRSA and MHRAT scores, r = –.40, p = .17, suggested that students who doubted their own reflexivity often demonstrated the most observable growth. This paradox captures the developmental essence of humility: it is most visible in those willing to remain teachable. Reflexivity and humility thus emerged as interdependent processes, deepening through iterative cycles of reflection and feedback. Findings affirm that structured reflection is both measurable and transformative. As students advanced through the Bass Model’s phases, they demonstrated increased capacity to connect personal values, professional ethics, and clinical practice. The reflective framework fostered self-awareness, cultural humility, and emotional resilience, qualities essential for navigating the moral complexities of modern midwifery. Reflection functioned not only as a learning strategy but also as a protective practice that mitigated burnout, moral distress, and value dissonance, enabling practitioners to sustain alignment with midwifery’s relational and justice-oriented foundations. By integrating reflection throughout the curriculum, this study offers a replicable model for cultivating ethically grounded, culturally responsive, and resilient practitioners. The Bass Model provides midwifery educators with a scaffolded, evidence-based pathway for teaching reflection as both skill and disposition, ensuring that learners internalize reflective habits capable of sustaining lifelong growth and professional integrity. This dissertation extends international research on the Bass Model of Holistic Reflection and contributes the first U.S. application within midwifery education. Its findings demonstrate that structured reflection can bridge the gap between midwifery philosophy and practice, equipping students to remain present, humble, and ethically centered amid systemic pressures. Reflection emerges here as a form of professional preservation, a means of keeping midwives connected to their purpose, their patients, and the philosophy that defines their care. In a healthcare landscape increasingly dominated by technocratic paradigms, structured reflection stands as a quiet revolution; one that preserves the heart of midwifery and sustains the integrity of those who practice it.
Keywords: Education, Pedagogy